(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2017)
This study was performed to compare the marginal microleakage of ormocer restorative material with that of giomer in vivo. Forty Class I cavities were prepared in non-carious permanent premolar teeth from 10 patients. Twenty cavities were filled with giomer and the remaining 20 cavities were filled by ormocer restorative materials. After one month, teeth were extracted, immersed in rhodamine dye solution, and then longitudinally bisected to assess the degree of dye penetration by stereoscopy. Furthermore, the gap between the dental material and tooth tissue were observed by the scanning electron microscope. The results showed that no microleakage (score 0) was detected in 15 ormocer and 5 giomer restorations. The remaining restorations were associated with dye penetration which was due to gap formation as seen in stereoscopic and scanning electron microscopic observations. The differences between ormocer and giomer restorative materials in respect to dye penetration were statistically significant. It can be concluded that ormocer restorative material shows less microleakage than that of giomer.